Normalized difference vegetation index sensor-based nitrogen management in bread wheat (Triticum aestivum L.): Nutrient uptake, use efficiency, and partial nutrient balance - Mitra, Biplab; Singha, Prantick; Roy Chowdhury, Arnab; Sinha, Abhas Kumar; Skalicky, Milan; Brestic, Marian; Alamri, Saud; Hossain, Akbar (Frontiers in Plant Science, 2023)
The present experiment was conducted to assess the impact of fixed and variable doses (using NDVI sensor) of nitrogen on wheat yields, nutrient uptake, nitrogen use efficiency (NUE) and soil nitrogen balance through optimization of N dose. There were ten treatments based on fixed and variable doses with various splitting, each replicated thrice under Randomised Complete Block Design (RCBD). It was revealed that application of a basal dose of 60 kg N ha-1, another 60 kg N ha-1 at crown root initiation (CRI) stage followed by NDVI sensor guided N application brought about a significant improvement in grain yields of wheat. It was seen that any curtailment in these doses at basal and CRI stages followed by N application through NDVI sensor later could not bring about higher crop yields. On an average, wheat crop responded up to 152-155 kg N ha-1 in both years. The maximum grain uptake was recorded in the said treatment while in contrast to grain N uptake, the straw N uptake was recorded maximum in N-rich plots where 225 kg ha-1 of N was applied. Partial factor productivity (PFPN) along with agronomic and economic NUE showed a decline trend with an increased rate of N application. Apparent N recovery (ANR) values were comparable in NDVI-based N application treatments with treatments receiving lesser N doses. Soil N status decreased in all the treatments except N rich strip where there was a marginal increase in soil N status after harvest of wheat crop in the rotation. Partial N balance was recorded as negative for all the treatments except the control.